1993
DOI: 10.1002/jcp.1041570211
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle activity and expression of prohibitin mRNA

Abstract: Prohibitin, a novel intracellular antiproliferative protein, blocks entry into the S phase of the cell division cycle when its mRNA is microinjected into normal fibroblasts or HeLa cells. To learn more about the interaction between prohibitin and the cell cycle, we studied the effect of microinjecting prohibitin mRNA at different points during the transition from G0 to S phase and analyzed prohibitin mRNA and protein levels in different parts of the cell cycle. The antiproliferative activity of microinjected p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
50
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 22 publications
3
50
1
Order By: Relevance
“…21,22 However, there is also study reported that PHB could contribute to the control of the S to G2 transition in the prostate cancer cells and cells containing PHB siRNA had an increase in cell population entering the S/G2 M phase. 23 Specifically 2% of these cells were detected in this phase when compared with control cells, which increased to 10% after the stimulation of dihydrotestosterone (DHT).…”
Section: Discussionmentioning
confidence: 99%
“…21,22 However, there is also study reported that PHB could contribute to the control of the S to G2 transition in the prostate cancer cells and cells containing PHB siRNA had an increase in cell population entering the S/G2 M phase. 23 Specifically 2% of these cells were detected in this phase when compared with control cells, which increased to 10% after the stimulation of dihydrotestosterone (DHT).…”
Section: Discussionmentioning
confidence: 99%
“…When microinjected into normal human fibroblasts, Phb1 mRNA attenuated DNA synthesis, however, this effect was subsequently shown to be mediated by the 3Ј-untranslated region rather than the coding region of the cDNA (52,53). The mechanism of cell cycle regulation was determined by Wang et al (54,55) who showed Phb1 could bind Rb as well as E2F1 to repress their transcriptional activity (56).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor suppressor genes are known to regulate both cell proliferation and cell death (9,40). Prohibitins act as negative regulators of cell proliferation in mammals and are implicated in tumor suppression (7).…”
Section: Discussionmentioning
confidence: 99%
“…7). Prohibitins negatively control the cell cycle in the early G 1 phase and specifically inhibit initiation of DNA synthesis (8,9). Prohibitin genes appear to be expressed in many tissues and organisms, but with some modulation of expression consistent with a role in the cell cycle (7,8,10).…”
mentioning
confidence: 99%